PENGARUH KARAKTERISTIK DEWAN DIREKSI TERHADAP PENGUKURAN KINERJA BANK DI INDONESIA - Susy Muchtar; Arifan Budianto Prabowo (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2009)
The purpose of this research is to analyse the effect of Characteristics of The Board of towar Directors s Bank Performance. This research was used are 19 banking firm which listed in Indonesian Stock Exchange during 2005-2008. Independent variables from this research are board size and Outside Director. Dependent variables are bank performance which include Net Interest Margin (NIM), Return On Asset (ROA), Return On Equity(ROE) and Efficiency Ratio. Control Variables are Size, Risk and Capital Ratio. The analysis method was used are multiple regression analysis. The result from this research shows that Board Size did not has related to bank performance. Outsiders has related to bank performance. Keywords: Board Size, Outside Director, Net Interest Margin (NIM), Return On Asset (ROA), Return On Equity(ROE) and Efficiency Ratio